RESEARCH ON MICROMYCETES IN OATS (AVENA SATIVA L.) UNDER THE CONDITIONS OF STUPINO DISTRICT, MOSCOW PROVINCE - J. I. Vargach; S. E. Golovin; I. G. Loskutov (Труды по прикладной ботанике, генетике и селекции)
Background. Fungal diseases are the main cause of the deterioration of grain quality and lower yield of cereals crops. Reduction of acreage, and, as a consequence, violation of crop rotation rules, oversaturation of fields with cereals, spring and summer droughts contribute to the mass emergence and widespreading of new obligate and facultative diseases in all regions of the country. Therefore, the search for a variety of donors and sources of sustainability is a vital task.Materials and methods. Materials engaged in the research were kernels of 41 oat accessions from the VIR collection of plant genetic resources, obtained in 2016–2018 in field crop rotations by the Genetic Diversity Research Department of ARHIBAN (Mikhnevo, Stupino District, Moscow Province). The specific diversity of micromycetes in grain was identified using Litvinov’s “wet chambers” technique and light microscopy.Results. The dominant pathocomplex of micromycetes in oat grain in Moscow Province was found to belong to the genera Alternaria (A. infectoria, A. tennuissima), Cladosporium (Cl. cladosporioides, Cl. herbarum) and Fusarium (F. avenaceum, F. culmorum, F. heterosporum, F. nivale var. nivale, F. oxysporum, F. poae, F. proliferatum, F. solani, F. sporotrichioides var. minus, and F. tricintum).Conclusion. The hulled cultivars ‘Bulanyi’ (VIR-15277, Russia, Moscow Prov.) and ‘Zakat’ (VIR-15384, Ukraine), and the naked cultivar Mestnyi (VIR-15290, UK) demonstrated the least contamination with pathogens: Fusarium fungi in these accessions were represented by one species – F. avenaceum.